Mammalian diversity of Carpish montane forest, Huánuco, Peru - Pacheco, Víctor (2019)
Despite the high diversity of the well-known mammals of Peru, there are few studies in the central yungas, which does not allow an adequate knowledge of their diversity. Here we present the results of an evaluation of mammal diversity of Carpish, Huanuco, a montane forest in a critical state of conservation. The study was carried out between 2001 and 2002 with five expeditions in the localities of Carpish de Mayobamba (2730 – 3080 m) and San Pedro de Carpish (1780 – 2400 m). We used capture methods, sightings and interviews, which represent an effort of 28 500 trap-nights and 190 net-nights. We recorded 35 species of mammals in the study area. The most diverse orders were bats and rodents (74.3%); these include four endemic species for the country, four species in some conservation category and the first record of the gracile opossum Gracilinanus aceramarcae for Huánuco. Species richness and diversity index (H' and Simpson) for rodents show no significant correlation with respect to elevation. The rodent Thomasomys ischyrus and the bat Anoura aequatoris were the species with the highest relative abundance. Our records, plus those from literature and review of scientific collections, support the occurrence of 45 mammal species in the Carpish forest. This species richness, endemism and the accelerated forest loss are the basis for recommending the establishment of a conservation area that guarantees the protection of the Carpish's montane forests.